2020
DOI: 10.1177/1847980420912601
|View full text |Cite
|
Sign up to set email alerts
|

Study on modification mechanism of workability and mechanical properties for graphene oxide-reinforced cement composite

Abstract: Graphene oxide/cement composite was prepared using a graphene oxide aqueous solution. The workability and mechanical properties of graphene oxide/cement composite with different concentrations for graphene oxide and the ratio of water to cement were investigated. The results observed were the fluidity of cement pastes decreased noticeably with the addition of graphene oxide and increased with the increase in the ratio of water to cement for all tested samples of different graphene oxide contents. It is indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 33 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…The distance between the electrode and the edge of the specimen was kept at 5 mm for all samples. The mixing, casting, demolding and curing processes for all specimens were similar to those in previous works [ 27 ]. To avoid effects caused by moisture and polarization, all specimens were dried for 27 h before testing.…”
Section: Methodssupporting
confidence: 54%
See 3 more Smart Citations
“…The distance between the electrode and the edge of the specimen was kept at 5 mm for all samples. The mixing, casting, demolding and curing processes for all specimens were similar to those in previous works [ 27 ]. To avoid effects caused by moisture and polarization, all specimens were dried for 27 h before testing.…”
Section: Methodssupporting
confidence: 54%
“…According to previous compressive strength test results [ 27 ], samples with w/c = 0.35 feature the best compressive strength, which increases by 24% compared to cement paste without GO. Thus, they were selected for the electrical resistivity test with different moisture contents when GO concentrations change from 0.05 to 0.2 wt.%.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Tong et al [ 24 ] found GO significantly improved the compressive strength of concrete but had little effect on its freeze-thaw resistance. At the same time, GO promoted the generation of high-density gels, reduced the porosity of the paste, and improved the chloride ion erosion resistance [ 25 ].…”
Section: Introductionmentioning
confidence: 99%